Travel Behavior of State Civil Servants of Ministry of Tourism and Creative Economy - Indrayani, I Gusti Ayu Putu Wita; Suprastayasa, I Gusti Ngurah Agung; Armeli, Armeli; Sucahyo, Purwastuti Eko (LACULTOUR: Journal of Language and Cultural Tourism, 2023)
This article aims to describe the tourist behavior of State Civil Servants of the Ministry of Tourism and Creative Economy of the Republic of Indonesia. Data was obtained by distributing questionnaires via Google form to staff. Of the fifty (50) people who were asked to fill in, as many as forty-one (41) or 82% filled it out. The data obtained were analyzed descriptively and the findings from this study were that the tourist behavior of state civil servants at the Ministry of Tourism and Creative Economy varied greatly. Most of the respondents travel between three to 6 times a year, like nature tourism, plan their trips within a week or less and between 3 to 6 months, travel between 2 to 3 days and between 4 to 6 days. Sources of information for their holidays mostly come from social media and from friends or colleagues. Most of them like to travel with their families and a few travels with friends, but no one travels alone.